Deduction of certain selection indices for carcass traits improvement depend on some body scales in ـJapanese quail - Abbas, Ahmed A.; Shukur, Ahmed M.; Husain, Firas; Al-Khatir, Bilal H.; Aljanabi, Thamer Kareem; Alta’ai, Salam M.; Mahdi, Aymen (Journal of Kerbala for Agricultural Sciences, 2017)
This study was carried out at the Poultry Research Station for Agricultural Research of the Livestock Section / Public Authority. This was used in the experiment 28/5/2013 of the data of 66 birds carcasses of Japanese Quail Selected according to body measurements. The study aimed to correlate a number of selection index that can be used in genetic improvement programs through the relationship of nonlinear regression and multiple regression, for the characteristics of the carcasses(weight of the carcass, and the weight of the chest and thigh segments and their proportions) based on a number of a live measurements of the Japanese quail at 49/days To be with (Weight of body and the length ,width and depth of chest ).Result showed higher R-square values for weight traits (weight of the carcass, and the weight of the chest and thigh) compared with proportions traits, which reflects values ​​that show fewer differences between the real values ​​and predicted values ​​of the carcass when it used as selection index, while the body measurements were the most important factor for the chest function, which is the result of breast yield (chest). The transaction is important and considered in the selection programs to improve., As well as a number of mathematical equations that can be considered as a means of measuring the carcass content and hence the possibility of using them as selection index to characterize the birds in the selection programs aimed at improving the characteristics of the carcass.